2009
DOI: 10.1111/j.1399-0004.2009.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous feature of isolated triphalangeal thumb–preaxial polydactyly linked to 7q36: no phenotypic difference between homozygotes and heterozygotes

Abstract: Preaxial polydactyly is a common limb malformation in humans with variable clinical expression. Different types of triphalangeal thumb-preaxial polydactyly phenotypes were mapped to the chromosome 7q36 region. We studied a large Turkish family of 69 individuals, of whom 22 individuals were affected. In all, 11 affected family members were clinically and radiologically evaluated. All affected individuals had a triphalangeal thumb and a preaxial (hypoplastic) extra digit bilaterally, with minimal intrafamilial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
5
25
0
Order By: Relevance
“…The mutation is shown to be present in three generations of affected individuals in a fully penetrant inheritance pattern with an invariable phenotype. This inheritance pattern has also been seen with most other ZRS mutations (Albuisson, et al, 2010; Farooq, et al, 2010; Semerci, et al, 2009). However some families with ZRS point mutations have variable phenotypes among affected individuals (Gurnett, et al, 2007; Lettice, et al, 2003) and at least one family is known to have reduced penetrance with phenotypically normal carriers (Gurnett, et al, 2007).…”
supporting
confidence: 57%
“…The mutation is shown to be present in three generations of affected individuals in a fully penetrant inheritance pattern with an invariable phenotype. This inheritance pattern has also been seen with most other ZRS mutations (Albuisson, et al, 2010; Farooq, et al, 2010; Semerci, et al, 2009). However some families with ZRS point mutations have variable phenotypes among affected individuals (Gurnett, et al, 2007; Lettice, et al, 2003) and at least one family is known to have reduced penetrance with phenotypically normal carriers (Gurnett, et al, 2007).…”
supporting
confidence: 57%
“…Point mutations were classified into two groups by Wieczorek et al [2010]: point mutations at position ZRS404 cause tibial hypoplasia/aplasia-polysyndactyly-triphalangeal thumb (Werner syndrome, OMIM 188770), while point mutations at other positions cause a variable phenotype of preaxial polydactyly/triphalangeal thumb [Lettice et al, 2003;Gurnett et al, 2007;Furniss et al, 2008;Semerci et al, 2009;Albuissin et al, 2011;Farooq et al, 2010]. One patient with a translocation (which led to physical separation of SHH and the ZRS) was reported to have preaxial polydactyly and triphalangeal thumb [Lettice et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…However, quite a few unconventional phenotypes were also appeared when the ZRS duplication was present. Actually, all individuals surveyed in this study have no malformed toe despite the fact that previous report involved with the phenotype of both hand and foot deformities31. ZRS-associated human limb malformations should be considered as a continuum of phenotypes with varied limb appearance such as the affected individuals in this study carried the ZRS duplication but showed no syndactyly phenotype either in hands or in feet.…”
Section: Discussionmentioning
confidence: 70%
“…These findings suggest that the interesting phenotype is hard to explain according to current genotype-phenotype mapping that only a point mutation of ZRS is sufficient to promote the expression of Shh in the anterior side of the limb bud and cause preaxial polydactyly, indicating the complexity of ZRS-associated human limb malformations. In addition to point mutation or small insertion/deletion within ZRS, the variants of ZRS also involve duplications of regions with varied length that contain ZRS and these duplications lead to a spectrum of outcomes ranging from TPTPS to SD411233031. It has been suggested that this group of limb defects caused by point mutations within ZRS or duplications around ZRS should be collectively referred to as ‘ZRS-associated syndromes’19.…”
Section: Discussionmentioning
confidence: 99%